Association between radiotherapy and risk of death from cardiovascular diseases in lung and bronchus cancer - Zhong Yi; Yu Zhang; Yu Zhang; Yu Zhang; Yu Zhang; Yu Wang; Yun Gao; Yanhong Wang; Xiangnan Li; Songwei Ru; Na Guo; Jingxuan Qiu; et al. (Frontiers in Cardiovascular Medicine, 2023)
BackgroundRadiotherapy plays an important role in the treatment of lung cancer. However, radiation-related deaths from cardiovascular disease (CVD) are a concern in these patients, and few studies have examined CVD-related death associated with lung cancer. We aimed to evaluate the risk of CVD-related death after radiotherapy in patients with lung and bronchus cancer.MethodsData were extracted from the surveillance, epidemiology, and end results database. Propensity score matching (PSM) was applied to reduce possible bias between patients who received radiotherapy and those who did not. The Kaplan–Meier method was used to estimate cardiovascular-specific survival (CVSS), and the log-rank test was used to compare CVSS between the radiotherapy and no radiotherapy groups. Cox proportional hazards regression analysis was performed to estimate the hazard ratio (HR) of CVD-related death.ResultsA total of 225,570 patients with lung and bronchus cancer were included, and 201,282 patients remained after PSM. Radiotherapy was identified as an independent risk factor for CVSS among patients with lung and bronchus cancer before PSM (HR: 1.18, P < 0.001) and after PSM (HR: 1.18, P < 0.001). Patients treated with radiotherapy had a significantly worse CVSS than those who did not receive radiotherapy before PSM (25-year CVSS: 49.9 vs. 56.4%, P = 0.002) and after PSM (25-year CVSS: 48.4 vs. 56.7%, P < 0.001). Radiotherapy was associated with more deaths from heart disease before PSM (81.9 vs. 77.2%, P < 0.001) and after PSM (83.0 vs. 78.7%, P < 0.001).ConclusionRadiotherapy is associated with an increased risk of CVD-related death, especially death from heart disease, in patients with lung and bronchus cancer. More efforts are needed to monitor cardiovascular health after radiotherapy.